The Effect of Cannabis Use and Cognitive Reserve on Age at Onset and Psychosis Outcomes in First-Episode Schizophrenia - Leeson, Verity C. (Oxford University Press, 2012)
Objective: Cannabis use is associated with a younger age at onset of psychosis, an indicator of poor prognosis, but better cognitive function, a positive prognostic indicator. We aimed to clarify the role of age at onset and cognition on outcomes in cannabis users with first-episode schizophrenia as well as the effect of cannabis dose and cessation of use. Methods: Ninety-nine patients without alcohol or substance abuse other than cannabis were divided into lifetime users and never-users of cannabis and compared on measures of premorbid function, cognition, and clinical outcome. Results: Cannabis users demonstrated better cognition at psychosis onset, which was explained by higher premorbid IQ. They also showed better social function and neither measure changed over the subsequent 15 months. Cannabis users had an earlier age at onset of psychosis, and there was a strong linear relationship between age at first cannabis use and age at onset of both prodromal and psychotic symptoms. Cannabis use spontaneously declined over time with 3-quarters of users giving up altogether. Later age at first cannabis use predicted earlier cessation of use and this in turn was linked to fewer positive psychotic symptoms and days in hospital during the first 2 years. Conclusions: Cannabis use brings forward the onset of psychosis in people who otherwise have good prognostic features indicating that an early age at onset can be due to a toxic action of cannabis rather than an intrinsically more severe illness. Many patients abstain over time, but in those who persist, psychosis is more difficult to treat.